Phosphonic group modified ruthenium-based catalyst, and preparation method and application thereof
Patent Information
- Application Number
- CN202611268124.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明为了解决现有技术提升RuO2催化剂的酸性OER稳定性,存在催化活性降低,制备过程复杂、成本高昂,难以兼顾活性与稳定性的同步提升的一系列问题,提供了一种磷酸基团修饰Ru基催化剂及其制备方法与应用
本发明提供的一种磷酸基团修饰Ru基催化剂及其制备方法与应用,通过在RuO2表面可控嫁接Pa分子,利用磷酸基团兼具质子受体加速反应动力学与共价键锚定提升稳定性的双重功能,克服了现有RuO2催化剂在酸性OER中活性与稳定性难以兼得的技术缺陷,实现了催化性能的全面协同提升。
Smart Images

Figure CN122918635A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology, and specifically relates to a Ru-based catalyst, namely a Ru-based catalyst modified with phosphate groups, its preparation method and application. Background Technology
[0002] Among numerous hydrogen production technologies, proton exchange membrane (PEM) water electrolysis offers advantages such as high current density, high gas purity, fast dynamic response, and good compatibility with renewable energy sources (wind, solar, etc.), making it a key technology for future green hydrogen production. However, the oxygen evolution reaction (OER) at the anolyte of PEM water electrolysis involves a four-electron-proton coupling transfer process, which is extremely slow and is the main bottleneck restricting overall energy conversion efficiency. Furthermore, the strongly acidic environment and high oxidation potential impose stringent requirements on the corrosion resistance and stability of the anode catalyst material.
[0003] Currently, iridium-based catalysts are recognized as commercially viable acidic OER electrocatalysts, but their scarcity and high cost make them unsuitable for large-scale industrial applications. Therefore, developing alternative catalysts has become a hot research topic. Among numerous candidate materials, ruthenium dioxide (RuO2) is considered a promising acidic OER catalyst due to its higher intrinsic activity and lower cost. However, RuO2 exhibits poor stability under acidic operating conditions and is easily oxidized to soluble RuO4. 2- The loss of active components and the collapse of catalyst structure lead to a lack of stability that is far from meeting the long-term operational requirements of industrial PEM water electrolysis.
[0004] To improve the stability of RuO2 catalysts in acidic OERs, researchers have explored various strategies, including ① preparing solid solution structures (such as RuIrOx); ② introducing other stable oxide supports or coatings (such as TiO2, SnO2, Sb2O3) and controlling the crystal planes, morphology, or defect structure of RuO2; and ③ heteroatom doping (such as F, B, Mn, Ni). While these methods have improved the stability of RuO2 to some extent, they often come at the cost of sacrificing some catalytic activity. Furthermore, the preparation processes are complex and costly, making it difficult to simultaneously improve both activity and stability. More importantly, most existing technologies focus on inhibiting Ru dissolution through "physical barriers" or "electronic structure modulation," rarely considering the synergistic enhancement of catalytic reaction kinetics and structural stability. This fails to fundamentally solve the technical challenge of achieving both activity and stability of RuO2 in acidic OERs.
[0005] Therefore, existing technologies still cannot solve the above problems simultaneously. Summary of the Invention
[0006] To address the problems of existing technologies in improving the acidic OER stability of RuO2 catalysts, such as reduced catalytic activity, complex and costly preparation processes, and difficulty in simultaneously improving activity and stability, this invention provides a phosphate-modified Ru-based catalyst, its preparation method, and its application.
[0007] This invention is achieved using the following technical solution: This invention provides a method for preparing a phosphate-modified Ru-based catalyst, comprising the following steps: S1, take 100~200 parts by mass of RuCl3·H2O and dissolve it in 20~60 parts by volume of anhydrous methanol, stir to obtain a mixed solution, and stir for ≥0.5h. The parts by mass are expressed in mg and the parts by volume are expressed in ml. S2, slowly add 0.1~0.4 volume parts of 80wt% hydrazine hydrate to the mixed solution prepared in step S1 and stir for ≥4h. After the reaction is completed, centrifuge, filter and collect the solid. S3, the solid collected in step S2 is washed with anhydrous methanol and ultrapure water alternately, and then freeze-dried for 10-20 hours to obtain the precursor catalyst. S4. Heat-treat the precursor catalyst prepared in step S3 at 300~500℃ for 1~4h. The heat treatment is carried out in a muffle furnace with a heating rate of 1~5℃ / min to obtain RuO2 catalyst. S5, take 10~100 parts by mass of the RuO2 catalyst prepared in step S4 and disperse it in 50 parts by volume of ultrapure water, stir evenly to obtain a mixed solution; then add 0.5 parts by volume of Pa (phytic acid), and continue stirring for 1~10h to obtain the Pa-treated RuO2 catalyst, denoted as RuO2@Pa.
[0008] The present invention also provides a Ru-based catalyst modified with phosphate groups prepared by the above preparation method.
[0009] Preferably, the Ru-based catalyst has a rutile phase structure, and O V / O L The ratio is higher than that of the unmodified RuO2 catalyst, wherein the P atoms in the Ru-based catalyst are uniformly distributed on the catalyst surface and form PO-Ru covalent bonds with Ru.
[0010] The present invention also provides the application of the above-mentioned Ru-based catalyst in the acidic oxygen evolution reaction, wherein the Ru-based catalyst is used as an anode electrocatalyst in the acidic water electrolysis oxygen evolution catalyst system.
[0011] In this invention, Pa is a naturally derived organic molecule containing six phosphate groups, each with multiple P-OH and P=O structures, exhibiting abundant coordination ability and proton activity. In recent years, Pa has been used to modify various metals (such as Co, Ni, Fe, etc.) or carbon-based materials for OER reactions under alkaline or neutral conditions. However, its application in acidic OER, particularly its combination with RuO2 and the mechanism of using phosphate groups as "proton acceptors" to accelerate the deprotonation process, has not been reported. Furthermore, the P atoms in phytic acid can form POM or PM-type covalent bonds with transition metals. This strong bonding is expected to anchor Ru sites and resist acid corrosion. By using a solvothermal method to controllably graft Pa molecules onto the RuO2 surface, the dual function of the phosphate groups in Pa—proton acceptor accelerating reaction kinetics and covalent bond anchoring enhancing stability—is utilized, simultaneously addressing the two core challenges of insufficient RuO2 activity and poor stability in acidic OER.
[0012] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a phosphate-modified Ru-based catalyst, its preparation method, and its application. By controllably grafting Pa molecules onto the surface of RuO2, the phosphate group combines the dual functions of proton acceptor to accelerate reaction kinetics and covalent bond anchoring to enhance stability. This overcomes the technical deficiency of existing RuO2 catalysts in achieving both activity and stability in acidic OERs, and realizes a comprehensive and synergistic improvement in catalytic performance.
[0013] This invention addresses the problems of slow OER reaction kinetics and high overpotential in traditional RuO2 catalysts. It utilizes the P-OH and P=O structures with six phosphate groups in the Pa molecule as highly efficient proton acceptors to promote the deprotonation step of the oxygen-containing intermediate ×OOH in the OER reaction, optimize the high energy barrier of the rate-limiting step, and thus promote the formation of OO bonds. This overcomes the shortcomings of traditional modification methods that often sacrifice activity for stability, significantly reduces the overpotential, and greatly improves the catalytic reaction kinetics.
[0014] This invention utilizes the stable PO-Ru covalent bond formed between P atoms in Pa and Ru to firmly anchor the Ru active sites on the oxide surface, making it difficult for them to detach from the crystal lattice even at high oxidation potentials. At the same time, a dense organic-inorganic hybrid network is formed on the catalyst surface, preventing corrosive species in the electrolyte from directly contacting the Ru active sites. This overcomes the shortcomings of existing technologies that cannot fundamentally inhibit Ru dissolution, providing a double-layer protection for enhancing catalyst stability and effectively improving its long-term operational stability under strongly acidic conditions.
[0015] The RuO2@Pa catalyst prepared by this invention exhibits excellent catalytic activity and structural stability, achieving 10 mA cm⁻¹ in 0.5 M H₂SO₄.-2 The required overpotential for the current density is only 205 mV, which is superior to C-RuO2 and the self-made RuO2 (H-RuO2). In a constant current test lasting up to 1200 h, it operated continuously with virtually no performance degradation. It significantly enhances the intrinsic catalytic activity while greatly improving structural stability. Moreover, it is simple to operate, operates under mild conditions, and is easy to use on a large scale, demonstrating significant innovation and promising prospects for industrial applications. Attached Figure Description
[0016] Figure 1 The image shows the SEM image of the catalyst prepared in Comparative Example 1.
[0017] Figure 2 The image shows a SEM image of the catalyst prepared in Example 1.
[0018] Figure 3 TEM image of the catalyst prepared in Comparative Example 1.
[0019] Figure 4 The image shows a TEM image of the catalyst prepared in Example 1.
[0020] Figure 5 The image shows the HRTEM image of the catalyst prepared in Comparative Example 1.
[0021] Figure 6 The image shows an HRTEM image of the catalyst prepared in Example 1.
[0022] Figure 7 This is an EDS mapping diagram of the catalyst prepared in Example 1.
[0023] Figure 8 The XRD patterns are for the catalysts prepared in Comparative Example 1 and Example 1.
[0024] Figure 9 Raman spectra of the catalysts prepared in Comparative Example 1 and Example 1.
[0025] Figure 10 Infrared spectra of the catalysts prepared in Comparative Example 1 and Example 1.
[0026] Figure 11 Ru 3p plots for the catalysts prepared in Comparative Example 1 and Example 1.
[0027] Figure 12 O 1s plots for the catalysts prepared in Comparative Example 1 and Example 1.
[0028] Figure 13 The p-2p diagram is for the catalyst prepared in Example 1.
[0029] Figure 14 Polarization curves of the catalysts prepared in Comparative Example 1, Example 1, Example 2 and Example 3.
[0030] Figure 15 Polarization curves of the catalysts prepared for Comparative Example 1, Comparative Example 2 and Example 1.
[0031] Figure 16 Tafel slope diagrams for the catalysts prepared in Comparative Examples 1, 2 and 1.
[0032] Figure 17 EIS diagrams of the catalysts prepared in Comparative Example 1 and Example 1.
[0033] Figure 18 C of the catalysts prepared for Comparative Example 1 and Example 1 dl Value graph.
[0034] Figure 19 The diagram shows the specific activity of the catalysts prepared in Comparative Example 1 and Example 1.
[0035] Figure 20 The image shows the in-situ EIS diagram of the catalyst prepared in Comparative Example 1.
[0036] Figure 21 The image shows the in-situ EIS diagram of the catalyst prepared in Example 1.
[0037] Figure 22 Comparison of charge transfer resistance at different potentials for the catalysts prepared in Comparative Example 1 and Example 1.
[0038] Figure 23 This is a graph showing the long-term stability test of the catalyst prepared in Example 1. Detailed Implementation
[0039] The specific embodiments of the present invention will be described in detail below.
[0040] Example 1 A method for preparing a phosphate-modified Ru-based catalyst includes the following steps: S1, dissolve 112.7 mg of RuCl3·H2O in 40 ml of anhydrous methanol, stir to obtain a mixed solution, and stir for ≥0.5 h.
[0041] S2, Slowly add 0.245 ml of 80 wt% hydrazine hydrate to the mixed solution prepared in step S1, and continue stirring the reaction for ≥5 h. After the reaction is completed, centrifuge and filter to collect the solid.
[0042] S3, the solid collected in step S2 was washed with anhydrous methanol and ultrapure water alternately, and then freeze-dried for 12 h to obtain the precursor catalyst.
[0043] S4. The precursor catalyst prepared in step S3 is heat-treated at 400℃ for 2h. The heat treatment is carried out in a muffle furnace with a heating rate of 1~5℃ / min to obtain the RuO2 catalyst.
[0044] S5, take 50 mg of the RuO2 catalyst prepared in step S4 and disperse it in 50 ml of ultrapure water, stir evenly to obtain a mixture; then add 0.5 ml Pa, continue stirring for 6 h to obtain the Pa-treated RuO2 catalyst, denoted as RuO2@Pa.
[0045] Example 2 A method for preparing a phosphate-modified Ru-based catalyst includes the following steps: In step S5, stirring was continued for 2 hours to obtain the Pa-treated RuO2 catalyst. The rest was completely consistent with Example 1, and the catalyst was denoted as RuO2@Pa-2h.
[0046] Example 3 A method for preparing a phosphate-modified Ru-based catalyst includes the following steps: In step S5, stirring was continued for 10 hours to obtain the Pa-treated RuO2 catalyst. The rest was completely consistent with Example 1, and the resulting catalyst was denoted as RuO2@Pa-10h.
[0047] Comparative Example 1 A method for preparing a Ru-based catalyst, retaining steps S1-S4 of Example 1, but omitting step S5 (i.e., without Ru treatment), yields a RuO2 catalyst, denoted as H-RuO2.
[0048] Comparative Example 2 Commercially available RuO2 powder was used as a reference catalyst and labeled C-RuO2.
[0049] Morphological structure characterization The RuO2@Pa prepared in Example 1 and the H-RuO2 prepared in Comparative Example 1 were characterized by scanning electron microscopy (SEM), and the results are as follows: Figure 1 , 2 As shown, both catalysts exhibit uniformly distributed nanoparticles, indicating that the RuO2@Pa prepared by phosphate group modification retains similar morphologies.
[0050] Transmission electron microscopy (TEM) characterization was performed on RuO2@Pa and H-RuO2, such as... Figure 3 , 4 As shown, both catalysts exhibit similar nanoparticle morphologies, with no large aggregated particles present, consistent with SEM observations.
[0051] High-lens transillumination (HRTEM) characterization was performed on RuO2@Pa and H-RuO2, and the results are as follows: Figure 5 , 6 As shown, both exhibit clear lattice fringes corresponding to different crystal planes, confirming that the original phase structure was maintained after modification with phosphate groups.
[0052] Unlike H-RuO2, the surface lattice of RuO2@Pa is locally distorted or weakened, see... Figure 6 The red-marked area in the middle indicates that the local Ru coordination environment of RuO2@Pa has changed.
[0053] Component analysis EDS surface scan analysis was performed on RuO2@Pa, and the results are as follows: Figure 7 As shown, the phosphorus element is uniformly distributed on the catalyst surface, indicating that the phosphate group has been successfully modified into RuO2.
[0054] X-ray diffraction characterization of RuO2@Pa and H-RuO2 was performed, and the results are as follows: Figure 8 As shown, the structure remains essentially unchanged after modification with phosphate groups, but the intensity of the diffraction peaks decreases. This indicates that the crystallinity of RuO2@Pa has decreased, suggesting a change in its local structure.
[0055] Raman spectroscopy was performed on RuO2@Pa and H-RuO2, and the results are as follows: Figure 9 As shown, the three main Raman peaks correspond to the structural vibration modes (E) of RuO2. g A 1g (and B2g), further confirming that RuO2@Pa retains the original structural features of H-RuO2.
[0056] Infrared spectroscopy tests were performed on RuO2@Pa and H-RuO2, and the results are as follows: Figure 10 As shown, a new diffraction peak (1171 cm⁻¹) appeared in RuO₂@Pa. -1 1075 cm -1 530 cm -1 These peaks are attributed to phosphate groups (-PO4). 3- This indicates that the phosphate group formed a PO-Ru bond with Ru in RuO2, which further confirms the incorporation of the phosphate group.
[0057] Electronic structure analysis X-ray photoelectron spectroscopy analysis was performed on Ru 3p of RuO2@Pa and H-RuO2, and the results are as follows: Figure 11 As shown, RuO2@Pa contains Ru 3+ / Ru 4+The proportion of is lower than that of H-RuO2, indicating that the valence state of Ru increases slightly after modification with phosphate groups, which helps to improve catalytic performance.
[0058] X-ray photoelectron spectroscopy analysis of O 1s of RuO2@Pa and H-RuO2 was performed, and the results are as follows: Figure 12 As shown, compared with H-RuO2, RuO2@Pa has fewer oxygen vacancies (O2, O2, and O2). V The binding energy of the peak shifted to a higher value, confirming that O V Changes in the chemical environment. Furthermore, O in RuO2@Pa V / O L The ratio (the ratio of oxygen vacancies to lattice oxygen) is higher than that of H-RuO2; the ratio of O is also higher. V / O L The ratio implies a decrease in steric hindrance, making it more likely that water will be released from the O2O zone. V On-site adsorption helps optimize the adsorption process of oxygen-containing intermediates, thereby accelerating the transfer of substances.
[0059] X-ray photoelectron spectroscopy analysis of the p 2p of RuO2@Pa yielded the following results: Figure 13 As shown, the fitting results indicate the presence of POM bonds, suggesting that the introduction of phosphate groups into RuO2@Pa forms a PO-Ru structure, which also confirms the introduction of phosphate groups into RuO2.
[0060] Performance testing Electrochemical performance was tested using a standard three-electrode system: the catalyst was drop-coated onto carbon paper as the working electrode (loading 1 mg·cm⁻¹). -2 A carbon rod was used as the counter electrode, Hg / Hg2SO4 as the reference electrode, and 0.5 M H2SO4 as the electrolyte. The test was conducted at room temperature and pressure.
[0061] Linear sweep voltammetry was performed on the catalysts prepared in Examples 1-3 and the comparative example, and the results are as follows: Figure 14 , 15 As shown, the best-performing RuO2@Pa catalyst reaches 10 mA cm⁻¹. -2 The overpotential required for the current density is only 205 mV, which is better than H-RuO2 (230 mV) and C-RuO2 (232 mV). Furthermore, RuO2@Pa maintains high OER activity as the voltage increases.
[0062] Tafel slope tests were performed on RuO2@Pa, H-RuO2, and C-RuO2, and the results are as follows: Figure 16 As shown, the Tafel slope of RuO2@Pa is the smallest, indicating that its reaction kinetics are the fastest. This proves that modifying RuO2 with phosphate groups greatly improves the reaction kinetics of the catalyst.
[0063] Electrochemical impedance spectroscopy was performed on RuO2@Pa and H-RuO2, and the results are as follows: Figure 17 As shown, RuO2@Pa has a low electrochemical impedance.
[0064] Double-layer capacitance (C) of RuO2@Pa and H-RuO2 dl The test results are as follows: Figure 18 As shown, RuO2@Pa and H-RuO2 have similar C values. dl The value indicates that the number of active sites is not a key indicator affecting performance improvement.
[0065] The specific activities of RuO2@Pa and H-RuO2 catalysts were tested, and the results are as follows: Figure 19 As shown, RuO2@Pa still exhibits the best catalytic performance after electrochemical active area correction, indicating that the intrinsic catalytic activity has been significantly improved.
[0066] In-situ EIS tests were performed on RuO2@Pa and H-RuO2 catalysts, and the results are as follows: Figure 20 , 21 As shown, compared to H-RuO2, RuO2@Pa has the smallest phase angle at each potential, indicating excellent mass transfer rate.
[0067] Impedance tests were performed on RuO2@Pa and H-RuO2 catalysts at different voltages, and the results are as follows: Figure 22 As shown, compared to H-RuO2, RuO2@Pa has the smallest impedance value at each potential, indicating an increase in electron transport rate.
[0068] Long-term stability tests were conducted on the RuO2@Pa catalyst, and the results are as follows: Figure 23 As shown, the catalyst performance remained stable after 1200 h of testing, indicating that phosphoric acid modification did indeed enhance the structural stability of RuO2 under acidic conditions.
[0069] The above experimental results corroborate each other, demonstrating the dual function of phosphate groups in acidic OERs: on the one hand, they act as proton acceptors to accelerate the deprotonation step, lower the reaction energy barrier, and enhance catalytic kinetics; on the other hand, they anchor the Ru active site through P-O-Ru covalent bonds and form an organic-inorganic hybrid network, inhibiting the peroxidation and dissolution of Ru and endowing the catalyst with excellent long-term stability.
[0070] In summary, this invention successfully prepared a high-performance RuO2 acidic OER electrocatalyst modified with phosphate groups through a simple and efficient liquid-phase reduction-thermal treatment method. This catalyst exhibits significant advantages in both activity and stability and has good prospects for industrialization.
[0071] The scope of protection claimed by this invention is not limited to the specific embodiments described above. Moreover, for those skilled in the art, this invention can have various modifications and alterations. Any modifications, improvements, and equivalent substitutions made within the concept and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A method for preparing a phosphate-modified Ru-based catalyst, characterized in that, Includes the following steps: S1, take 100~200 parts by mass of RuCl3·H2O and dissolve it in 20~60 parts by volume of anhydrous methanol, stir to obtain a mixed solution, wherein the parts by mass are expressed in mg and the parts by volume are expressed in ml; S2, slowly add hydrazine hydrate dropwise to the mixed solution prepared in step S1 and stir to react. After the reaction is completed, centrifuge, filter and collect the solid. S3, the solid collected in step S2 is washed with anhydrous methanol and ultrapure water alternately, and then freeze-dried to obtain the precursor catalyst; S4. Heat-treat the precursor catalyst prepared in step S3 at 300~500℃ for 1~4h to obtain RuO2 catalyst; S5, take the RuO2 catalyst prepared in step S4 and disperse it in 50 parts by volume of ultrapure water, stir it evenly to obtain a mixed solution; then add Pa and continue stirring for 1~10h to obtain the Pa-treated RuO2 catalyst, denoted as RuO2@Pa.
2. The method for preparing a phosphate-modified Ru-based catalyst according to claim 1, characterized in that, In step S1, the stirring time is ≥0.5h; in step S2, the stirring time is ≥4h; in step S3, the freeze-drying time is 10~20h; and in step S4, the heating rate of the heat treatment is 1~5℃ / min.
3. The method for preparing a phosphate-modified Ru-based catalyst according to claim 1, characterized in that, In step S2, the amount of hydrazine hydrate added is 0.1~0.4 parts by volume, and the concentration is 80 wt%.
4. The method for preparing a phosphate-modified Ru-based catalyst according to claim 1, characterized in that, In step S5, the mass-to-volume ratio of the RuO2 catalyst to Pa is 10~100:0.
5.
5. A Ru-based catalyst for phosphate group modification prepared by any of the preparation methods in claims 1 to 4.
6. The Ru-based catalyst modified with a phosphate group according to claim 5, characterized in that, The Ru-based catalyst exhibits a rutile phase structure, O V / O L The ratio is higher than that of the unmodified RuO2 catalyst.
7. The Ru-based catalyst modified with a phosphate group according to claim 5, characterized in that, In the Ru-based catalyst, the P atoms are uniformly distributed on the catalyst surface and form PO-Ru covalent bonds with Ru.
8. The application of the Ru-based catalyst according to claim 5 in the acidic oxygen evolution reaction.
9. The application of the Ru-based catalyst according to claim 8, characterized in that, The Ru-based catalyst is used as an anode electrocatalyst in an acidic water electrolysis oxygen evolution catalyst system.